Treatment of hypernatremia in neonatal calves with diarrhea - Abutarbush, Sameeh M. (Canadian Veterinary Medical Association, 2007)
Five hypernatremic, diarrheic, neonatal calves were treated mainly by the intravenous administration of 5% dextrose alone or with isotonic sodium bicarbonate. All calves recovered without complications. The average reduction rate of serum sodium concentration was about 4 times that recommended and has not been tried successfully before in hypernatremic scouring calves.